Jami' Al-Anwar Mosque as a Medium to Strengthen the Influence of Islam in Teluk Betung Lampung in The 19th Century - Budianto, Aan; Hariizan, Muhammad Akhdan; Ammbiya, Muhammad Vanji; Luvi, Maylatul (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
There is the oldest mosque in Lampung located in the South Teluk Betung area, which houses several historical relics depicting the movement of change in Islam, namely Masjid Jami' al-Anwar. This mosque has stood since the Dutch colonial era and holds the uniqueness of how it has played a role in strengthening the development of Islam in Teluk Betung. Therefore, this research attempts to gather information related to the early development of Masjid Jami' al-Anwar in Teluk Betung, Lampung. The method used in this research is a historical method starting from data collection and exploration of sources from mosque archives, related journals, and several articles. Then, to further strengthen the existing data, the author conducted interviews involving direct sources who are descendants of the founders of Masjid Jami' al-Anwar. The results of the research show that Masjid Jami' al-Anwar is used as a place of teaching that has a significant influence on the growth of Islam in Teluk Betung to Tanjungkarang through mosque management networks.